Dynamic Capabilities of Universities in the Knowledge Economy - BEJINARU, Ruxandra (Management Dynamics in the Knowledge Economy, 2017)
The purpose of this paper is to analyze how universities can develop dynamic capabilities based on their strategic resources in order to increase their competitiveness in the knowledge economy. ”Dynamic capabilities” is a concept introduced by Teece, Pisano, and Shuen (1997) to emphasize the managerial capacity of a given organization of using efficiently its strategic resources in transforming opportunities in business success. They reflect the capacity of the organization to sense, seize, adapt to the changing environment. For a university, the most important strategic resources are information, knowledge, and ideas which constitute its intellectual capital. The present paper is analyzing critically these strategic resources of a university and the necessary conditions to develop dynamic capabilities in order to use efficiently these resources in a turbulent economic environment. Universities are in the knowledge economy the most important hubs for knowledge creation and its transfer to the students, as well as to their communities. At the same time, professors contribute to the development of the generic thinking skills of their students to help them for employability in a future with many new jobs and new business activities.